PWE-054 Infliximab therapeutic drug monitoring in IBD virtual biologics clinic leads to durable results. (8th June 2018) - Selinger, Christian; Lenti, Marco; Clark, Tanya; Rafferty, Helen; Gracie, David; Ford, Alex; O'Connor, Anthony; Ahmad, Tariq; Hamlin, John; Sagar, Rebecca
Abstract : Introduction: We have previously shown that therapeutic drug monitoring (TDM) of infliximab (IFX) trough levels and anti-drug antibodies (ADAS) can aid decision making for patients on biological therapy, in conjunction with clinical symptoms, disease history and investigations. The aims of this follow-up study were to evaluate 1 year outcomes of patients who had decisions changed on the basis of TDM results in our original study, and to test the hypothesis that TDM-based decisions to alter or stop IFX treatment are safe and durable. Methods: In our original study, a blinded treatment decision was first made, without knowledge of IFX trough and ADAs. Immediately after this, TDM results were released and a final treatment decision was recorded. For this study we collected long-term clinical outcomes 12 months after the decision. We compared patients with changed treatment decisions with those where the decision to continue IFX remained unchanged. We defined changed decision groups as (I) IFX stopped, (II) switch to other biological therapy, and (III) continue IFX with adjusted dose or interval. Events of interest were hospitalisation for IBD or further changes to biological therapy. Results: Of 190 patients reviewed in virtual biologics clinic 54 (28%) had decisions changed in the light of results of TDM. Of the 136 patients with an unchanged decision, 128 who continued IFX as previously dosed were used as the comparator group. There were no differences in hospitalisation rates between 3 changed decision groups (I, p=1), (II, p=0.2), (III, p=0.4) and the unchanged decision comparator group (table 1). Similarly, we found no differences in subsequent biologic therapy switches between 3 changed decision groups (I, p=1), (II, p=1), (III, p=0.2) and the unchanged decision comparator group. Conclusion: Our study demonstrates that changes to IFX treatment based on TDM were durable. Patients with a decision to stop, switch, or continue with an adjusted IFX dose experienced comparable clinical outcomes with those who continued IFX therapy unchanged. TDM-based decisions about IFX treatment that incorporate the clinical picture can safely alter therapy without exposing patients to an increased risk of hospitalisation or need for subsequent changes to biologic therapy.